Evaluation of the implementation process of a new emergency triage system: West coast system for triage (WEST) - Samah Habbouche; Eric Carlström; Per-Arne Svensson; Carl Magnusson; Lina Dahlen Holmqvist (PLoS ONE, 2026)
Background Emergency Department (ED) crowding has escalated globally and has been associated with delayed treatment and increased short-term mortality. In western Sweden, several EDs transitioned from the Rapid Emergency Triage and Treatment System (RETTS©) to the West coast system for triage (WEST), based on principles of the South African Triage Scale. While WEST was introduced and spread rapidly and may have potential benefits, reports suggested challenges during its implementation. Objective This study examined the implementation of WEST at the first two EDs (ED1 and ED2) and identified barriers and facilitators. The study focused on the transition from RETTS© to WEST and explored staff experiences across implementation stages. Methods The study used a qualitative descriptive design with a mixed-methods approach and included semi-structured individual interviews with 36 triage nurses from two hospitals (ED1 n = 17; ED2 n = 19). Interviews explored experiences with WEST, implementation challenges, and comparisons with RETTS©, using Rogers’ “Diffusion of Innovations” as a sensitizing framework and treating each ED as a distinct social system. A deductive qualitative content analysis guided by Rogers’ Diffusion of Innovations was conducted, with inductive coding of unexpected themes from the final open question. Descriptive analyses of Likert-scale items complemented the qualitative analysis. The study received ethical approval, and written informed consent was obtained from all participants before interviews. Results ED1 participants expressed great enthusiasm and perceived WEST as a notable improvement. ED2 responses were more varied, with reservations commonly targeting the implementation process and concurrent organizational changes. Across both sites, most nurses (30/36) perceived WEST as more accurate than RETTS© in identifying critically ill patients. Conclusions Implementing WEST was feasible but context dependent. Information, motivation, and consensus-building, education, and organizational readiness emerged as important factors in the implementation process. Viewing each ED as a distinct social system, with its own culture and readiness for change, helped explain why adoption of WEST varied between sites.